The Dynamic of Location Attributes Toward Malaysian Real Estate Investment Trust Performance - Abdul Jalil, Rohaya; Sarrazin Mohammad, Izran; Chai Ping, Tiong (International Journal of Engineering and Technology, 2018)
The Malaysian real estate investment trusts (M-REITs) properties intensive location contributes toward higher rental yield. Nevertheless, the location diversification depends on the type of properties in the portfolio, puzzled shareholder in their investment decision making in M-REITs. This study aim to determine the dynamic of location attributes toward financial performance. The pearson correlation and descriptive analysis of ten years (2006 until 2015) data is used. This study indicate that there is correlation between attributes of economic location with dividend yield(DY) (cor: 0.241). Yet, the market capitalization, have a negative correlation (cor: -0.246), which contradict with prior study on REITsâ€™ location attributes. This study also show that attributes of location of M-REITs properties should located between 5km to 10km from central business district (CBD).This study conclude that in order to ensure M-REITs properties remain competitive for commercial occupancy. The investment on M-REITs proven that dynamic of location attributes is priority, which support that M-REITs design for a long term investment goal.Â Â